First 100 total hip arthroplasties performed by a young surgeon using the direct anterior approach: learning curve and complications - Li, Yen-Wei; Yu, Shang-Won; Yeh, Jih-Hsi; Ma, Ching-Hou; Yen, Cheng-Yo; Tu, Yuan-Kun (Archives of orthopaedic and trauma surgery, 2024)
Introduction Most of the reported discussions about the learning curve for the direct anterior approach (DAA) in total hip arthroplasty (THA) have been by experienced surgeons. The study’s aim was to describe the learning curve, short-term outcomes, complications, and adaptations to the DAA used in the first 100 THA cases experienced by a young surgeon who had received DAA training for trauma surgeries. Materials and methods This retrospective study summarizes the first 100 consecutive cases experienced by a young surgeon who performed the unilateral DAA for THA between 2019 and 2021. Cumulative sum (CUSUM) analysis was performed to evaluate the learning curve on the basis of operative time and overall complications. The demographics data, short-term outcomes, and complications of the first 50 and second 50 cases were compared. Results The CUSUM curve declined after 49 and 55 cases, measured by operative time and overall complications, respectively. The median operative time (104 vs. 80 min) and intraoperative fluoroscopic time (38 vs. 12 s) increased significantly in the first 50 cases compared with the times in the second 50 cases. Complications tended to occur in the first 50 cases (12% vs. 6%), and the overall rate was 9%. Major complications all occurred in the first 50 cases, with a rate of 4%. Only one case, which involved a complicated periprosthetic fracture around the stem that extended to the tip, required the intervention of a senior surgeon. Conclusions Even after receiving training on the DAA for trauma surgeries, the young surgeon experienced a steep learning curve and more complications in the first 50 cases. The DAA for THA is a technically demanding procedure and may require guidance from an experienced surgeon to manage unexpected complications.